Plant- and Stand level variation in biophysical and physiological traits along tree density gradients in the Cerrad - Scholz, Fabian Gustavo (2008)
The objective of this study was to characterize and understand morphological and physiological variation in traits related to water economy, at the plant and stand level, along a gradient of tree density in a Neotropical savanna (Cerrado). Cerrado plots subjected to long-term fertilization and gallery forests were also included in the analysis to expand the axes of ecosystem variation. Consistent changes in stand level biophysical traits observed along the gradient of increasing tree density included a decrease in weighted-average wood density, and increases in leaf surface area per plant, leaf specific hydraulic conductivity, specific leaf area and stomatal conductance. A conceptual model of biophysical, morphological and physiological trait interactions was developed in an attempt to explain determinants of hydraulic architecture and variations in water economy of Cerrado trees. Consistent with the model minimum leaf water potentials were higher, during the dry season, in low wood density trees compared to high wood density trees, and higher leaf water potential was associated with higher stomatal conductance. On the other hand, variations in stand level physiological and morphological traits along the tree density gradient could not be explained by variations in single environmental factors. Some of the potential contributing factors are: higher concentration and availability of soil nutrients in the upper portion of the gradient where tree density is greatest and constrains to tree establishment and growth by waterlogging and presence of concretions in the soil profile where tree density is lowest. Key words: gallery forest, hydraulic architecture, nutrients, savannas, specific leaf area, wood densitygallery forest, hydraulic architecture, nutrients, savannas, specific leaf area, wood density